METHODS OF INNOVATIVE MANAGEMENT OF PERSONNEL IN THE LIBRARY-INFORMATION SYSTEM - Goyibova Sayyora Usmonovna (Bright Mind Publishing, 2025)
This article provides detailed information on the methods of innovative management of personnel in the library information system, state support of innovative activities, and determination of the effectiveness of the activities of innovation entities.
Keywords: Innovative activities, innovation entities, activity effectiveness, state policy, concept of innovative management of personnel.